Green energy carriers and energy sovereignty in a climate neutral European energy system. (July 2023) - Wetzel, Manuel; Gils, Hans Christian; Bertsch, Valentin
Abstract: Meeting the goals of the Paris Agreement poses significant challenges to provide renewable energy for the power, heating, transport, and industrial sector. Both green hydrogen and methane are considered key energy carriers for reaching these climate targets. However, future needs for an effective infrastructure deployment are highly uncertain, particularly concerning the timely and substantial expansion of renewable electricity generation in Europe. To better understand the trade-offs between domestic production and large-scale energy imports and their corresponding infrastructures needs, we use the energy system optimisation model REMix. We consider different strategic European story lines and constraints on expansion of pipelines and power grids to identify robust capacity targets from a cost optimal perspective. The results indicate that European energy sovereignty is feasible but comes at around 3% higher cost compared to stronger cooperation with resource-rich areas such as the British Isles or the Maghreb region. In contrast, preventing any network expansion lead to an increase of up to 15%. With regard to the extensive adaptations of energy infrastructures required to achieve the emission reduction goal, the timely and substantial expansion of electricity generation from renewable sources in particular is to be regarded as crucial. Highlights: European energy sovereignty comes at slightly higher cost compared to international cooperation. Strategic narratives have high impact on national and European infrastructure needs. Repurposing of natural gas pipelines enables large-scale transport of green hydrogen. Production of green hydrogen is sited in areas rich in renewable energy. Combining concentrated solar power and photovoltaics supports the production of low-cost green methane.